Formulation and in-vitro evaluation of stavudine extended release tablets - Sarad Pawar Naik Bukke; Rajesh Asija; M. Purushothaman (International Journal of Pharmacy and Analytical Research, 2022)
During the past two decades, there has been a steady increase in both the number of antiretroviral medications and the number of possible regimens available to manage human immunodeficiency virus (HIV) and acquired immune deficiency syndrome (AIDS). But still, regimen fails due to some reasons such as toxicity, adverse effects, and consequent difficulties with patient adherence. Stavudine is the Food and Drug Administration approved drug for clinical use for the treatment of HIV infection, AIDS, and AIDS related conditions, either alone or in combination with other antiviral agents. The side effects of Stavudine are dose dependent and a reduction of the total administered dose reduces the severity of the toxicity. To reduce the frequency of administration and to improve patient compliance, a once daily sustained release formulation of Stavudine is desirable. Hence, in the present work, an attempt has been made to develop once daily sustained release matrix tablets of Stavudine using putative hydrophilic matrix materials such as hydroxyl propyl methyl cellulose (HPMC) K15M, Sodium CMC and PEO. The prepared extended release tablets were then evaluated for various physical tests like diameter, thickness, weight variation, hardness, friability, and drug content uniformity. The results of all these tests were found to be satisfactory. Formulation and evaluation properties given best result by the extended release tablets of Stavudine.